2011
DOI: 10.1111/j.1365-3024.2010.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase binds to and kills Entamoeba histolytica trophozoites

Abstract: During amebic invasion, neutrophils are a key component in either protecting against invading trophozoites or contributing to tissue damage. Upon degranulating or being lysed, neutrophils release toxic substances that can kill amebas as well as damage host tissue. In a previous study we identified a protein from nonspecifically stimulated peritoneal exudates of hamster that has peroxidase and marked amebicidal activity. In the current study we analyzed the in vitro amebicidal effect of purified hamster myelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…In general, these bands were located between 75 and 100 kDa, above 50 kDa and around 37 kDa. The 50 and 37 kDa protein sizes are consistent with earlier electrophoresis data on purified equine MPO and with immunoblotting data on lysates of human MPO‐containing tissues . Especiallly in nonreducing conditions, MPO can occur as a tetrameric enzyme (∼150 kDa) with 2 β‐ (or light) and 2 α‐ (or heavy) subunits .…”
Section: Discussionsupporting
confidence: 87%
“…In general, these bands were located between 75 and 100 kDa, above 50 kDa and around 37 kDa. The 50 and 37 kDa protein sizes are consistent with earlier electrophoresis data on purified equine MPO and with immunoblotting data on lysates of human MPO‐containing tissues . Especiallly in nonreducing conditions, MPO can occur as a tetrameric enzyme (∼150 kDa) with 2 β‐ (or light) and 2 α‐ (or heavy) subunits .…”
Section: Discussionsupporting
confidence: 87%
“…It was shown previously for human neutrophils that a partial disorder of MPO production resulted in a reduced ability to produce NETs, while a total absence of MPO inhibits NET formation . Thus, MPO may likely bind directly to the surface of N. fowleri trophozoites to carry out amoebicidal activity using H 2 O 2 produced by the amoebas themselves as was reported for Entamoeba histolytica . Ferrante et al .…”
Section: Discussionmentioning
confidence: 70%
“…The result also suggests that MPO can bind to the N. fowleri surface, similar to that observed with Entamoeba histolytica trophozoites. 46 On the other hand, we observed that N.…”
Section: Discussionmentioning
confidence: 77%